Within these minds - Tan, Ervin En Ming (Nanyang Technological University, 2022)
Within These Minds is a contemplative exploration into the minds of Young-Onset Dementia (YOD) individuals, journeying with them through the psychological, emotional and relational struggles that result from the diagnosis. The film is centred around two YOD individuals, Alison and Steven, alongside their respective caregivers Jamie and Steven, delving into how each of them have coped with their diagnosis whilst facing the inevitable deterioration of the condition.